3.2: Distinguished Student Paper: High Image Quality Wearable Displays with a Fast‐Response Liquid Crystal. Issue 1 (June 2015) - Lou, Zhenyue; Peng, Fenglin; Chen, Haiwei; Hu, Minggang; Wu, Shin‐Tson
Abstract : We report two ultra‐low viscosity liquid crystals for high image quality wearable displays with a field sequential color LCOS. Our mixtures offer ~4X faster response time than a commercial material at 20°C and ~8X faster at −20°C. Such a fast response time offers vivid color, high ambient contrast ratio, low power consumption, and mitigated color breakup even at −20°C. Different LC modes and frame rates are also evaluated.